FACTORS RELATED TO THE INCIDENCE OF ANEMIA IN PREGNANT WOMEN IN THE TRIMESTER III IN THE WORKING AREA OF THE MEURAXA COMMUNITY HEALTH CENTER, BANDA ACEH CITY - Humaira, Ayu; Naimah, Naimah; Akbar, Fahrisal (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2024)
Background: Anemia in pregnant women remains a significant public health issue in Aceh. According to the 2017 Aceh Provincial Health Profile, the prevalence of anemia among pregnant women reached 87%. In Banda Aceh City, Meuraxa Health Center recorded the highest rate in 2016 at 26.25%, which increased to 28.60% in 2017, despite educational efforts regarding iron tablet intake and proper nutrition. Method: This study employed an analytical quantitative design with a cross-sectional approach. The sample consisted of all third-trimester pregnant women with anemia in the working area of Meuraxa Health Center, Banda Aceh City, from January to December 2018, totaling 47 participants, selected using total sampling. Result: Parity (p=0.001), where multiparous and grand multiparous women were at higher risk of severe anemia. Nutritional status (MUAC) (p=0.000), with undernourished women more likely to experience severe anemia. ANC visits (p=0.002), where fewer ANC visits increased the risk. Compliance with iron tablet consumption (p=0.001), where non-compliance was associated with a higher risk of severe anemia. Husband support (p=0.026), where lack of support was associated with increased risk. Recommendation: It is recommended that third-trimester pregnant women regularly check their Hb levels and involve their husbands as supporters in anemia prevention. Health professionals play a crucial role in providing information and counseling to reduce the incidence of anemia.